Problematika Ekonomi Kapitalis dan Sosialis Perspektif Ismail Raji Al-Faruqy - Muh. Ikbal; Nindi Dwi Tetria Dewi; Helmi Syaifuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
There is no doubt that the developing and well-known economic system today is a capitalist and socialist economic system. The basic concepts in the capitalist economy are the freedom of property rights for each individual, economic freedom and free competition. Likewise with the basic principles of socialist economy, namely the absence of private property rights, the existence of economic equality and political discipline, namely the state is under labor regulations. In Islam, the life of the world is always closely related to the concept of the hereafter. Meanwhile, capitalism and socialism separate morality from theology. By using descriptive analytical method, this research produces several conclusions; First, the economic problems that have occurred cannot be separated from the thoughts that arise on the state of society at that time with the frequent developments of the times and thoughts. Second, capitalism and socialism emerged as new ideological guidelines that emerged from colonial circles due to the lust for the situation that occurred so as to give rise to complete control on the part of the individual and to the exclusion of morals and religion. Third, Al-Faruqi’s thoughts on the concept of monotheism can provide a solution to the lack of scientific values that also affect people's mindsets. So from the results of the study it can be concluded that if a science is successful it will destroy all aspects of life both in terms of ideology or morals.